Imposition of Tax Law on Cryptocurrencies and NFT in Indonesia - Anggia Debora Sitompul (Fakultas Hukum Universitas Lampung, 2022)
This research aims to look at the potential of government revenue through taxes on digital currencies or better known as cryptocurrencies and against digital assets called NFT. With normative research methods to analyze how cryptocurrencies and digital assets (NFT) should be taxed at low or high tax rates. In addition to understanding cryptocurrency taxation policies as well as NFT, the study also looked at the taxation policies of various countries on cryptocurrencies and digital assets. Each country has different guidelines and considerations for the legal status and policies of the regulation of cryptocurrencies and NFT. There is no consensus between countries about this.